No ecological opportunity signal on a continental scale? Diversification and life‐history evolution of African true toads (Anura: Bufonidae). (12th July 2016) - Liedtke, H. Christoph; Müller, Hendrik; Rödel, Mark‐Oliver; Menegon, Michele; Gonwouo, LeGrand Nono; Barej, Michael F.; Gvoždík, Václav; Schmitz, Andreas; Channing, Alan; Nagel, Peter; Loader, Simon P.
Abstract : The niche‐filling process predicted by the "ecological opportunity" (EO) model is an often‐invoked mechanism for generating exceptional diversity in island colonizers. Whether the same process governs lineage accumulation and trait disparity during continental colonization events is less clear. Here, we test this prediction by investigating the rate dynamics and trait evolution of one of Africa's most widespread amphibian colonizers, the true toads (Bufonidae). By reconstructing the most complete molecular phylogeny of African Bufonidae to date, we find that the diversification of lineages in Africa best conforms to a constant rate model throughout time and across subclades, with little support for EO. Evolutionary rates of life‐history traits have similarly been constant over time. However, an analysis of generalists and specialists showed a shift toward higher speciation rates associated with habitat specialization. The overall lack of EO signal can be interpreted in a number of ways and we propose several explanations. Firstly, methodological issues might preclude the detection of EO. Secondly, colonizers might not experience true EO conditions and due to the size, ecological heterogeneity and age of landmasses, the diversification processes might be more complex. Thirdly, lower speciation rates of habitat generalists may have affected overall proliferation of lineages.